Boron adatom adsorption on graphene: A case study in computational chemistry methods for surface interactions - Jubin, Sierra; Rau, Aaditya; Barsukov, Yuri; Ethier, Stephane; Kaganovich, Igor (Frontiers in Physics, 2022)
Though weak surface interactions and adsorption can play an important role in plasma processing and materials science, they are not necessarily simple to model. A boron adatom adsorbed on a graphene sheet serves as a case study for how carefully one must select the correct technique from a toolbox of computational chemistry methods. Using a variety of molecular dynamics potentials and density functional theory functionals, we evaluate the adsorption energy, investigate barriers to adsorption and migration, calculate corresponding reaction rates, and show that a surprisingly high level of theory may be necessary to verify that the system is described correctly.